2003
DOI: 10.1152/ajprenal.00401.2002
|View full text |Cite
|
Sign up to set email alerts
|

A role for angiotensin II AT1receptors in ureteric bud cell branching

Abstract: Gene-targeting studies in mice demonstrate that the renin-angiotensin system is required for the proper development of the renal medulla. In the absence of angiotensin II (ANG II) or the ANG II type 1 (AT1) receptor, mice exhibit poor papillary development and a severe urinary-concentrating defect. These findings imply that the ureteric bud (UB) and its branches are targets for ANG II actions during renal development. However, direct evidence linking ANG II with UB-branching morphogenesis does not exist. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
60
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 43 publications
3
60
0
4
Order By: Relevance
“…As noted above, increased apoptosis has been hypothesized as a mechanism through which a prenatal perturbation could result in decreased nephron endowment. Blockade of the AT1R has previously been reported to inhibit ureteric branching morphogenesis (16). Our data show differential effect of DEX on the AT1R subtypes, with an increase in AT1Ra and a decrease in AT1Rb.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…As noted above, increased apoptosis has been hypothesized as a mechanism through which a prenatal perturbation could result in decreased nephron endowment. Blockade of the AT1R has previously been reported to inhibit ureteric branching morphogenesis (16). Our data show differential effect of DEX on the AT1R subtypes, with an increase in AT1Ra and a decrease in AT1Rb.…”
Section: Discussionsupporting
confidence: 64%
“…These last two genes are of great interest as recently, Dickinson et al (10) reported that 60 h of DEX exposure to pregnant Spiny mice increased expression of both BMP-4 and TGF-␤1 in the fetal metanephroi. The renal renin-angiotensin system (RRAS) has also been shown to be important in kidney development with the major receptor the angiotensin II type 1 receptor (AT1R) able to regulate ureteric branching morphogenesis as well as renal growth (16). This is of great importance as maternal DEX exposure alters the expression of fetal angiotensin II receptors in other models of DEX exposure (17).…”
mentioning
confidence: 99%
“…Renin mRNA and protein were also found to be expressed at low levels in the connecting tubule of mice during salt restriction (22,23). The presence of renin mRNA in the medulla at least under some circumstances and our evidence for transient medullary activity of the renin promoter during development would add a mechanistic aspect to the notion that angiotensin II may be involved in kidney development and in particular in the morphogenesis of the branching ureteric bud (8). In agreement with this concept, renin-angiotensin system-deficient mouse models are consistently characterized by papillary atrophy and concentrating defects (5,15,32,35).…”
Section: Discussionmentioning
confidence: 52%
“…Quantitative analysis of murine Ang II receptors AT 1 R and AT 2 R gene expression indicate that AT 1 R undergo a progressive increase during fetal and neonatal life, whereas AT 2 R are high in the fetus and decline significantly with maturation (11). Immunolocalization studies demonstrated that AT 1 R and AT 2 R are expressed in the UB and its early branches of embryonic day 12 (E12) mouse embryos, whereas angiotensinogen and renin are expressed in the stromal mesenchymal cells that surround the UB branches (12)(13)(14). The localization of RAS components in the stroma and UB provided the initial suggestion that paracrine signaling through RAS-AT receptors may…”
mentioning
confidence: 99%
“…In vitro studies have shown further that UB cells that are isolated from E11.5 mouse embryos express AT 1 R that are functionally coupled to the mitogen-activated protein kinase (MAPK) pathway (15). UB cells that are seeded in collagen gels form cellular cords and tubular structures, and treatment with Ang II increases the number and the complexity of these cellular branches (12). Ang II-induced UB cell branching is mediated in part via the AT 1 R because it is abrogated by the specific AT 1 R antagonist candesartan.…”
mentioning
confidence: 99%